DEVELOPMENT OF INDIRECT SANDWICH ELISA METHOD FOR DETERMINATION OF RECOMBINANT DARBEPOETIN - Izzati, Arfa
Darbepoetin (DPO) is a glycoprotein hormone by stimulating colony forming units erythroid (CFU-E) to increase the production of erythrocytes. DPO has 5 Nlinked chains and 1 O-linked chain with the potential maximum number of sialic is 22 molecules. An extra 2 N chains gives DPO greater metabolic stability in vivo compared to the previous generation. Detection of DPO concentrations using ELISA has previously been used commercial kits but the cost of commercial kits is quite expensive and needs to be done developing and validating indirect-sandwich ELISA methods in-house to measure DPO levels produced by Chinese Hamster Ovary (CHO) cell scale research and development. Optimal coating antibody results dilution at 1:6000. An indirect-sandwich ELISA in-house method was designed that meets all requirements to fulfill this goal. The method has a linear range 2.29-73.40 ?g/mL with coefficient correlation (R)=0.9959. Accuracy is obtained in the range of 100-103%. Intra-day and inter-day precision is 0.46- 8.44% and 3.44-9.33%. LOD and LOQ were 0.2767 ?g/mL and 0.9224 ?g/mL, respectively. The cost analysis showed that the ELISA method in-house assay is cheaper than the existing commercial sandwich ELISA kits.